The Role of Telecentres in Providing Internet Services For Teacher In Rural Areas - Febriany, Febriany (IAINU Kebumen, 2022)
The gap between urban and rural areas still occurs in Indonesia. There are still numerous remote and underdeveloped areas that still require special attention from the government. The gap does not only take place in terms of knowledge but also in facilities and infrastructure in accessing the technology. Pandauke Village is a remote village, not only in terms of geographically but also demographically. PLIK is a form of telecenters which is an innovation expected to reduce the gap. The role of teachers in remote village is quite important that they are demanded to keep improving their professionalism. This research is aimed to view the attributes of innovation in PLIK, in terms of teacher opinions in Pandauke Village. The present research employed qualitative method with descriptive analysis presentation. The results of this research show that 5 innovations, namely Relative Advantage, Compatibility, Complexity, Trialability and Observability are also considered important by teachers to adopt an innovation, in this respect is PLIK located in Pandauke Village